Knowledge of reproduction and safe sex among teenagers from a highschool in Fortaleza– Ceará - Façanha, Mônica C.; Menezes, Beatriz L.F.; Fontenele, Ana D.B.; Melo, Marina A.; Pinheiro, Adivânia S.; Carvalho, Cecília S.; Porto, Ivna A.; Pereira, Larissa O.C. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction:adolescents and young adults constitute a group of increasing risk for sexually transmissible diseases (STD), including HIV infec-tion. The greatest vulnerability of the young people comes from inconsistencies in the use of condoms associated to the raising taxes of sexual acti-vity with different partners. Objective:this study aims to evaluate the knowledge of adolescents from a high school about: reproductive physiology;risk factors for DST/HIV infection, as the sexual behavior and to evaluate the frequency of routine use of condom. Methods: auto-managed question-naire was applied to 100 students of a High school from Fortaleza. Results:of the 98 that answered if already had had sexual relations, 38.8% saidyes. Fifty - two students answered correctly the duration of the menstrual cycle. The girls did it right 2.28 times plus than boys (p<0.01). About thebest time to get pregnant, 30 answered it right. The females did right 39% more than males (p=0.057). From those who already had sexual intercour-se, 33(91.7%) they said to have used condom in the last one, while 21 (58.0%) said that they had used in all intercourses in the last 6 months.Conclusion:the proportion of high school students who knows about menstrual cycle is small, especially among those of the masculine sex, and theuse of condom is irregular.